Standardized Opioid Counseling Is Underperformed Before and After Anterior Cruciate Ligament Reconstruction - Ehab M. Nazzal, M.D; Rajiv P. Reddy, B.S; Rebecca M. Haley, M.D; Jacob M. Wilson, M.D; Joseph D. Lamplot, M.D; Volker Musahl, M.D; John W. Xerogeanes, M.D (Elsevier, 2023)
Purpose: To characterize contemporary pain management strategies after anterior cruciate ligament reconstruction (ACLR) within the US and international orthopaedic community. Methods: This was a cross-sectional survey-based study disseminated to a consortium of expert orthopaedic surgeons in the management of anterior cruciate ligament injuries. The survey was a 27-question, multiple choice-style questionnaire with question topics ranging from demographic characteristics and practice characteristics to surgeon-specific pain management strategies in the postoperative period after ACLR. Specific topics of interest included the use of preoperative opioid education and/or counseling sessions, implementation of standardized pain management regimens, use of pain tracking systems, and use of any adjunct non-narcotic analgesic modalities. Results: A total of 34 completed surveys were collected, representing a 73.9% response rate. Over 85% of respondents reported prescribing opioids as a standardized postoperative regimen after ACLR. Surgeons reported prescribing 5- to 10-mg doses, with the tablet count ranging anywhere from fewer than 10 tablets to more than 20 tablets, often instructing their patients to stop opioid use 2 to 4 days postoperatively. Prescribed dosages remained stable or decreased over the past 6 months with increased use of non-narcotic adjuncts. Only one-third of respondents reported using standardized preoperative opioid counseling, with even fewer discussing postoperative discontinuation protocols. Conclusions: Over 85% of respondents prescribe opioids as a standardized postoperative regimen after ACLR, with only 15% providing non-narcotic pain regimens. However, prescribed dosages have remained stable or decreased over the past 6 months with increased use of non-narcotic adjuncts. Only one-third of respondents use standardized preoperative opioid counseling, with even fewer discussing postoperative discontinuation protocols. Clinical Relevance: The ongoing opioid epidemic has created an urgent need to identify the most effective pain management strategies after orthopaedic procedures, especially ACLR. This study provides important information about current pain management practices for patients who have undergone ACLR.